The electrochemistry and modelling of hydrogen storage materials - Kalisvaart, W.P.; Vermeulen, P.; Ledovskikh, A.V.; Danilov, D.; Notten, P.H.L. (Journal of alloys and compounds, 2007)
Mg-based alloys are promising hydrogen storage materials because of the high gravimetric energy density of MgH 2 (7.6 wt.%). A major disadvantage, however, is its very slow desorption kinetics. It has been argued that, in contrast to the well-known rutile-structured Mg hydride, hydrided Mg-transition metal alloys have a much more open crystal structure facilitating faster hydrogen transport. In this paper, the electrochemical aspects of new Mg–Sc and Mg–Ti materials will be reviewed. Storage capacities as high as 6.5 wt.% hydrogen have been reached with very favourable discharge kinetics. A theoretical description of hydrogen storage materials has also been developed by our group. A new lattice gas model is presented and successfully applied to simulate the thermodynamic properties of various hydride-forming materials. The simulation results are expressed by parameters corresponding to several energy contributions, for example mutual atomic hydrogen interaction energies. A good fit of the lattice gas model to the experimental data is found in all cases.